Organizational commitment and quality of life at work among public health nurses in Israel. Issue 4 (4th April 2019) - Aharon, Anat A.; Madjar, Batya; Kagan, Ilya
Abstract: Objective: To test the relationship between job satisfaction, professional self‐image, work environment, organizational commitment (OC), and quality of life at work (QoLW) among public health nurses in Israel. To determine which variables can predict OC and QoLW among public health nurses. Design and Sample: One hundred and thirty‐two public health nurses participated in this cross‐sectional study with a structured self‐administered questionnaire that examined OC, professional self‐image, job satisfaction, nursing work environment, and QoLW. Pearson correlation tested correlations between variables and multiple regression was conducted to predict OC and QoLW. Measurements: The five measurements (job satisfaction, professional self‐image, work environment, OC, and QoLW) based on validity questionnaires with high internal confident. Results: All five variables showed a significant positive correlation. Job satisfaction ( t = 5.77, p < 0.001) and nursing work environment ( t = 4.55, p < 0.001), contributed significantly to the explanation of OC and QoLW variance. Nursing work environment ( t = 6.42, p < 0.01) and job satisfaction ( t = 2.99, p < 0.01) were the variables that predicted QoLW. Conclusions: Nursing managers should be proactive and create a professional environment for nurses to encourage their OC and QoLW as factors that may influence public health nurses.